A meta-analytic review of the impact of ethnomathematics-based instruction on students’ conceptual understanding in mathematics - Prasetyawan, Enggar; Masitoh, Lisda Fitriana (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2025)
Ethnomathematics-based learning has been implemented in various regions as an approach to mathematics education. This meta-analysis investigates the overall effectiveness of ethnomathematics-based instruction in enhancing students' conceptual understanding of mathematics, while also examining the extent to which study characteristics influence its impact. The literature search was carried out for studies published between 2018 and 2023 using the Google Scholar database, facilitated by Harzing’s Publish or Perish software. As a result of the screening process, eight studies that fulfilled the predefined inclusion criteria were selected for data extraction. Data analysis was performed using the OpenMEE software, employing a random-effects model for effect size estimation. The findings indicated a substantial overall effect size of 1.330, suggesting that ethnomathematics-based learning exerts a significant positive influence on students' conceptual understanding of mathematics. Analysis of study characteristics revealed that studies conducted at the elementary school level, employing cluster random sampling and involving fewer than 30 participants, demonstrated greater effectiveness of ethnomathematics-based learning. These findings may serve as considerations for mathematics education practitioners in implementing ethnomathematics-based learning in the future. In particular, the results highlight the urgency for teachers and curriculum developers to integrate local cultural contexts into mathematics instruction as a strategy to foster deeper conceptual understanding, increase student engagement, and support equitable learning outcomes.